Factors Influencing Stock Price of Nepalese Commercial Banks - Pramod Dahal; Ramjee Puri (HM Journals, 2021)
This study employs data from 10 out of 20 banks (using purposive or judgmental sample techniques) during a ten-year period (2012/13 to 2021/22), comprising 100 observations, to investigate the variables affecting the stock price of Nepalese commercial banks. With an emphasis on internal variables like earnings per share (EPS), dividend per share (DPS), and price-earnings ratio (P/E Ratio), as well as external variables like gross domestic product (GDP), inflation (INF), and money supply (MS), it uses a descriptive and causal comparative study design. Notably, the study emphasises the significance of EPS and P/E Ratio in stock pricing, in line with other studies from around the world. The unexpected result that there is a negative association between GDP and Market Price per Share (MPS) calls into question accepted wisdom and highlights the necessity for economic research particular to Nepal. The study also demonstrates how inflation negatively affects MPS, highlighting the need for careful inflation assessments in the banking industry. On the plus side, it emphasises how important Money Supply (M2) is in influencing stock values. These observations provide insightful guidelines for future analysis and strategic choices pertaining to Nepal's banking industry.